The Use Of Xylazine For Caudal Epidural Analgesia in Cows (Journal of Hama University, 2020)
Twenty-five mature Holstein cows were given a single 5 mL epidural injection of one of four different concentrations of xylazine or saline. The onset, magnitude and duration of caudal epidural analgesia was quantitated with the use of a low   voltage DC current applied to the perineal area. The dose that produced the longest duration of analgesia and produced the least ataxia or sedation was approximately 0.05 mg/kg (25 mg in 5 mL diluent). The analgesia produced by this xylazine dose was compared to a standard dose of epidural lidocaine (100 mg/5 mL) by the same method. To investigate the role of systemic absorption in the production of epidural analgesia, the previously utilized epidural xylazine dosage was given intramuscularly to four adult cows. Analgesia was quantitated as before and the results are compared with epidural xylazine. Epidural xylazine produced a significantly greater duration of analgesia, as measured by this model, than did epidural lidocaine. Xylazine, given epidurally, produced greater perineal analgesia than did xylazine given IM.